Quick and Easy Screening for Vitamin D Insufficiency in Adults: A Scoring System to Be Implemented in Daily Clinical Practice. Issue 7 (February 2016) - Deschasaux, Mélanie; Souberbielle, Jean-Claude; Andreeva, Valentina A.; Sutton, Angela; Charnaux, Nathalie; Kesse-Guyot, Emmanuelle; Latino-Martel, Paule; Druesne-Pecollo, Nathalie; Szabo de Edelenyi, Fabien; Galan, Pilar; Hercberg, Serge; Ezzedine, Khaled; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Vitamin D is essential regarding several health outcomes. Prevention of insufficiency (25-hydroxyvitamin D concentration ≤20 ng/mL) generally entails blood testing and/or supplementation, strategies that should target at-risk individuals because blood testing is costly, and unwarranted supplementation could result in vitamin D overload with unknown long-term consequences. Our objective was to develop a simple score (Vitamin D Insufficiency Prediction score, VDIP) for identifying adults at risk of vitamin D insufficiency. Subjects were 1557 non–vitamin D-supplemented middle-aged adults from the SU.VI.MAX cohort. Scoring points corresponded to the rounded odds ratio for each individual-level characteristic associated with vitamin D insufficiency in a multivariable logistic regression model. Receiver operating characteristic curve (area under curve), sensitivity, specificity, and positive and negative predictive values were computed. External validation was performed in an independent cohort (NutriNet-Santé, N = 781). For female sex, overweight, low physical activity, winter season, moderate sun exposure, and very fair or dark skin 1.5 points were attributed; 2 points for latitude ≥48°N and spring season; 2.5 points for obesity and late winter; 3 points for low sun exposure. Points were then summed up for each participant. The VDIP score had an AUC = 0.70 ± 0.01 (validation: 0.67 ± 0.02). With a score of 7 or more, 70% of the participants were vitamin D-insufficient (80% in those with a score ≥9), sensitivity/specificity were 0.67/0.63, and positive and negative predictive values were 0.70/0.59. The VDIP score performed well in identifying middle-aged adults at risk of vitamin D insufficiency (score ≥7, moderate risk; score≥9, high risk), using only simple individual-level characteristics easily assessable in day-to-day clinical practice. Implementation of this simple and costless score could thus obviate unwarranted supplementation and/or blood testing.